Translanguaging Practices of Multilingual Learners of German - Annabell Sahr (Athens Institute for Education and Research, 2020)
This qualitative case study draws on a theoretical framework of translanguaging (García & Wei, 2014) and border pedagogies (Cashman, 2015) and seeks to shed light on the question of what role translanguaging can play in students' language learning in a German as a foreign language class at a Hispanic-serving university that is situated in the United States-Mexico borderland. This case study focuses on 18 students who were part of a larger participatory action research study (Lichtman, 2013), which includes focus groups, individual interviews, as well as audio-recordings of classroom discussions that were transcribed and analyzed using thematic analysis. The data highlights translanguaging as a language learning practice that also contributes to reflections on identity formation and language choice in an educational climate that is often hostile towards immigrant cultures and languages.